A baseband processor for pulsed ultra-wideband signals - Blazquez, R.; Newaskar, P.P.; Lee, F.S.; Chandrakasan, A.P. (2004 IEEE Custom Integrated Circuits Conference, 2004)
This paper presents a baseband processor for pulsed ultrawideband signals. It consists of an analog to digital converter (ADC), a clock generation system and a digital back-end. The FLASH interleaved ADC provides four bit samples at 1.2 GSPS. The back-end uses parallelization to process these samples and to reduce the signal acquisition time to 70 /spl mu/s. The baseband processor was implemented in the same 0.18 /spl mu/m CMOS chip as a part of a complete transceiver. A complete 193 kbps wireless link is demonstrated.